Конструкції функцій Ляпунова в теорії регулярних лінійних розширень динамічних систем на торі - Кулик, В.Л. (Український математичний журнал, 2015)
Рассматриваются функции Ляпунова в виде линейной комбинации квадратичных форм. Исследуются условия регулярности линейных расширений динамических систем на торе. Lyapunov functions are considered in the form of linear combinations of quadratic forms. We study the conditions under which the linear extensions of dynamic systems on a torus are regular.